Freedom and change - Gilmore, John T.; Allen, Beryl M.; McCallum, Dian (Hodder Education Caribbean history, 2019)
Provide students with a solid foundation in Caribbean history and encourage social studies skills, with an active approach to the study of social history for Lower Secondary. - Ensure full coverage with content spanning history from ancient civilisations to more recent 21st Century events. - Prepare students for studies at CSEC level with a solid grounding in Caribbean history. - Provide practice in many different skill areas with activities, including 'What would you do?' problem solving activities. - Encourage students to compare and contrast past events with more recent ones with 'Then and Now' feature. - Inspire interest with relevant archaeological information from the region as well as career options related to the subject as part of the 'Did you know?' feature. - Reinforce learning and test knowledge through comprehensive revision questions.